The fabrication and characterization of Al/SiC-MMC castings produced by vacuum assisted solidmould investment casting process - Guler, KeremAltug; Kisasoz, Alptekin; Karaaslan, Ahmet (PLEIADES PUBLISHING INC, 2013)
In this paper, a promising manufacturing approach to cast metal matrix composites is proposed. In order to produce metal matrix composites by investment casting, SiC preforms were fabricated in 3D structure. Afterwards, A6063 aluminium alloy matrix material was infiltrated into preforms which were placed in the solid investment casting moulds with vacuum assistance. Preforms were characterized using Archimedes' test, scanning electron microscope ana X-ray diffraction analysis. Also, fabricated cast specimens, were characterized using hardness tests, image analysis and scanning electron microscope observations. The results show that, in the vacuum assisted solidmould investment casting method; infiltration, of the preforms by molten metal was successfully achieved. Moreover, hardness of the composite higher than the matrix up to ratio of 100% by SiC reinforcement and T6 heat treatment.
Keywords: AlMMC; SiC; investment casting; preform; MATRIX; MICROSTRUCTURE; INFILTRATION; Metallurgy & Metallurgical Engineering